Pelatihan Pembuatan Perangkat Pembelajaran Menggunakan Model Pembelajaran Inovatif dalam Rangka Implementasi K-13 Bagi Guru-Guru Sekolah Menengah Pertama (SMP) di Desa Iluta, Kecamatan Batudaa - Abd Haris Odja; Ritin Uloli (Univeristas Negeri Gorontalo, 2022)
The KKN-Thematic Village Building Activity Program aims to carry out learning device manufacturing training using innovative learning models in the framework of K-13 implementation. The method used in the KKN-Thematic Village Building program is training in making learning devices using innovative learning models in the framework of K-13 implementation. This is done to increase understanding to junior high school teachers, namely the creation of learning devices using innovative learning models in the framework of K-13 implementation.Curriculum 2013 is a new curriculum applied by the government to replace the Education Unit Level Curriculum that has been in force for approximately 6 years. The 2013 curriculum entered probation in 2013 by turning some schools into probation schools.